Pola Pemanfataan Sumberdaya Laut Berbasis Kearifan Lokal Pada Masyarakat Wabula, di Kabupaten Buton - Tamar Mustari; Sulhan Manaf; La Ode Abdul Munafi (SIMULACRA: JURNAL SOSIOLOGI, 2019)
The research describes the patten of utilization of marine resources based on local wisdom in the Wabula community in Buton district. The data were collected by doing interwiews, observation, documentation, and study of literature. Then the data were analyzed descriptively and kualitatively. The results showed that in utilizing marine resources, Wabula community have a local wisdom called kaombo which is protected marine areas by the custom. When a marine area is designated as a kaombo a ban om the explotation of marine resources in the area applies. The prohibition is intended to provide a respite for the continuation of the proliferation of marine biota in kaombo ecosystem. A violation of the prohibition is subject to strict customary law. To preserve the local wisdom of Wabula community in the utilization of marine resources, then through the regulation of  Buton Regent Number 13 of 2018, Wabula was designated as an area Customary Law Community in the management of marine resources based om local customary law. The regulation is considered as an ideal model for strengthening local community institutions in conserving marine resources in a sustainable manner.